Fabrication of composite microfluidic devices for local control of oxygen tension in cell cultures. Issue 2 (14th December 2018) - Gao, Yandong; Stybayeva, Gulnaz; Revzin, Alexander
Abstract : We developed a microfabrication strategy that integrated two materials with different gas permeability in a single microfluidic chip to enable local control of oxygen tension for cell cultures. Abstract : Oxygen tension is a central component of the cellular microenvironment and can serve as a trigger for changes in cell phenotype and function. There is a strong need to precisely control and modulate oxygen tension in cell culture systems in order to more accurately model the physiology and pathophysiology observed in vivo . The objective of this paper was to develop a simple, yet effective strategy for local control of oxygen tension in microfluidic cell cultures. Our strategy relied on fabrication of microfluidic devices using oxygen-permeable and impermeable materials. This composite device was designed so as to incorporate regions of gas permeability into the roof of the cell culture chamber and was outfitted with a reservoir for the oxygen-consuming chemical pyrogallol. When assembled and filled with pyrogallol, this device allowed oxygen depletion to occur within a specific region of the microfluidic culture chamber. The geometry and dimensions of the hypoxic region inside a microfluidic chamber were controlled by features fabricated into the oxygen-impermeable layer. Oxygen tension as low as 0.5% could be achieved using this strategy. To prove the utility of this device, we demonstrated that hypoxia induced anaerobic metabolism in a group of liver cancer cells, and that neighboring cancer cells residing under normoxic conditions upregulated the expression of transporters for taking up lactate – a product of anaerobic respiration. The microfluidic devices described here may be broadly applicable for mimicking multiple physiological scenarios where oxygen tension varies on the length scale of tens of micrometers including the cancer microenvironment, liver zonation, and luminal microenvironment of the gut.